The Reconstruction of the Implementation from Business Judgment Rule Doctrine in Individual Limited Liability Companies: A Progressive Legal Review - Lumentut, Lisma; Palullungan, Liberthin (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Individual Company is part of a legal reform which is based on efforts to empower small and medium enterprises. Individual Company are intended to empower the community's economy so that the leaders of individual Company need to receive protection through the business judgment rule doctrine.Purposes of the Research: This study aims to formulate a legal prescription related to the implementation of the doctrine in the conception of the business judgment rule in individual companies in terms of a progressive legal perspective.Methods of the Research: Normative law with a concept and statutory approach.Results of the Research: The relevance of the implementation of the business judgment rule doctrine for individual company can also increase the competitiveness of individual company because it can increase innovation from the leaders of individual company to be more optimal and maximal in managing individual company and not be afraid of the various risks that exist. Viewed from a progressive legal perspective, the reconstruction of the implementation of the business judgment rule doctrine for individual company can be carried out through analogical legal constructions because individual company and are generally the same in substance. In order to optimize the implementation of the business judgment rule doctrine for individual company, it is necessary to establish special rules governing guidelines and instructions in implementing the business judgment rule doctrine for individual company.